Microplastics in the Surface Sediment of the main Red River Estuary - Le, Nhu Da; Hoang, Thi Thu Ha; Duong, Thi Thuy; Phuong, Ngoc Nam; Le, Phuong Thu; Nguyen, Tien Dat; Phung, Thi Xuan Binh; Le, Thi My Hanh; Le, Thi Lien; Vu, Thi Huong; et al. (Vietnam Journal of Earth Sciences, 2022)
Microplastics (< 5mm) are one emerging pollutant in the environment. These are the threats and challenges facing the global environment, economy, and society, especially in hotspot regions such as Asia. This paper presents the microplastic characteristics found in the surface sediment of the main Red River estuary (the Ba Lat) during four separate monitoring runs in 2020. The microplastic amount in the sediment samples varied from 800 items per kg of dried weight (dw) to 3,817 items.kg-1 dw, averaging 2,188 ± 1,499 items.kg-1 dw. Fiber and fragment microplastics were discovered to be primary shapes, of which fibers dominated (94%). Microplastic fiber sizes were found mainly in the < 500 µm (69%) range. The most primarily observed colors of microplastics were blue (36%), white (21%), and red (11%). There were five recognized polymer types (polypropylene (PP), polyethylene (PE), polyurethane (PU), polyamide (PA), and polystyrene (PS)) in the sediment samples, with PE and PP predominating. Seasonal fluctuations in microplastic concentrations at the Ba Lat site, a significant aquaculture zone, may indicate the contribution of multiple sources. Our research demonstrated the necessity of microplastic observation in organisms, particularly in the aquaculture zones in Vietnam. Our findings further underline the importance of managing and minimizing the amount of plastic garbage that enters the ecosystem.